CHARACTERISTICS AND STABILITY ASSESSMENT OF LIPOSOMAL PREPARATIONS - M. V. Dmitrieva; T. A. Timofeeva; N. A. Oborotova; I. I. Krasnyuk; O. I. Stepanova (Разработка и регистрация лекарственных средств)
The main objective of pharmaceutical technology is to maximize the use of «pharmaceutical factors» for ensuring the high quality of prepared medicines, which coincides with the strategic task of biopharmacy, which is to maximize the effectiveness of medicines and reducing to the maximum of their possible adverse effect on the body According to biopharmaceutical studies, dosage form substantially affect the validity of the included medicinal substances. In recent decades, a significant part of scientific research in the field of pharmacy is devoted to the creation of dosage forms based on targeted delivery systems of diagnostic and medicinal substances, among which liposomes have gained the greatest popularity. Liposomes are considered as promising delivery systems of drugs in the bloodstream because of its colloid properties, controlled size, surface characteristics, membranotropic and biocompatibility. However, the colloidal disperse systems are thermodynamically unstable, so the undoubted practical relevance in the development stage and the obtaining of liposomes presents a characterization and evaluation of stability of the resulting product. For this purpose, as a rule, use 3 core indicators - size of vesicles, polydispersity index and zeta-potential. The size of liposomes is one of the main indicators of the quality of liposomal preparation, which mainly depends on its component composition and technology. Dispersion of liposomes significantly affects the rate of elimination and distribution of the drug, the concentration in biological fluids and tissues, as well as determines the mechanism of cell internalization. Since in most macromolecular and nanodisperse systems molecules and particles are not the same, when describing the properties of systems, it is necessary to use the particle distribution functions according to their parameters, i.e. in the study of real systems to take into account their polydispersity, since monodisperse approximations can lead to incorrect conclusions about the properties of particles. The width of the particle size distribution is characterized by the polydispersity index. Zeta-potential is an important indicator of the surface charge of particles and a measure of electrostatic interaction (repulsion or attraction) between particles, as well as one of the main parameters affecting the stability of dispersed systems. Liposomes with high negative or positive zeta-potential repel each other and remain monodisperse and stable, and with low zeta-potential - are able to unite, aggregate and form unstable compounds. In addition, this parameter also allows you to predict the interaction of liposomes and cells.